Development of Infographic Teaching Materials for the Events of the September 30, 1965 Movement in Indonesian History Learning at SMAN 1 Kudus - Agustin, Nur Anisa; Pramono, Suwito Eko; Romadi, Romadi (Universitas Negeri Semarang, 2020)
The purpose of this study includes: (1) Analyze the history of the Incident Movement of 30 September 1965, which was done in SMA N 1 Kudus. (2) Analyze the infographic history of the Incident Movement of 30 September 1965 that corrects of students needed in SMA N 1 Kudus. (3) Analyzing the infographic feasibility of the history Incident Movement of 30 September 1965 as a teaching material. This research uses the Research and Development (R & D) method and is then grouped into three research stages: preliminary stage, development, and evaluation. The results of this study indicate that the teaching materials used in SMA N 1 Kudus are from Worksheet and the student book of Curriculum 2013. After passing the validation stage, the infographic teaching materials of the G30S 1965 Event have gained eligibility for use in school without revision. Based on student and teacher responses of infographic teaching materials showing a positive reaction to use infographic in teaching history as teaching material, that is proven by the response questionnaire from teacher and students.